2012
DOI: 10.1088/0953-2048/25/9/095018
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the critical current density in MgB2wires doped with Ni nanoparticles

Abstract: Iron-sheathed MgB2 wires doped with 0, 1.3 and 2.52 wt% carbon protected nickel superparamagnetic nanoparticles (the average diameter of the particles is 20 nm) and sintered at 650 °C were prepared. X-ray diffraction patterns and magnetization measurements showed that neither substitution of C for B nor substitution of Ni for Mg occurred during the synthesis process. Scanning electron microscopy imaging of the doped sample revealed a homogeneous distribution of nickel particles within the MgB2 matrix. Transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
(90 reference statements)
3
20
0
1
Order By: Relevance
“…Researchers adopted either in-situ route using Mg/B powder mixtures with phase formation during a heat treatment or exsitu route using pre reacted MgB 2 powder as precursor and found that the properties of bulk MgB 2 samples are crucially affected by the preparation technique. Significant improvement in critical current carrying capacities of in-situ MgB 2 by various additives and nanoparticles [5][6][7][8][9][10][11][12][13][14] was observed, as the substitution reaction can easily occur via this route. For the application purpose, due to fewer fabrication parameters, ex situ method is more attractive and has been utilized by many researchers for making wires 15,16 and tapes.…”
Section: Introductionmentioning
confidence: 98%
“…Researchers adopted either in-situ route using Mg/B powder mixtures with phase formation during a heat treatment or exsitu route using pre reacted MgB 2 powder as precursor and found that the properties of bulk MgB 2 samples are crucially affected by the preparation technique. Significant improvement in critical current carrying capacities of in-situ MgB 2 by various additives and nanoparticles [5][6][7][8][9][10][11][12][13][14] was observed, as the substitution reaction can easily occur via this route. For the application purpose, due to fewer fabrication parameters, ex situ method is more attractive and has been utilized by many researchers for making wires 15,16 and tapes.…”
Section: Introductionmentioning
confidence: 98%
“…The possibility of long-range pinning by magnetic nanoparticles prompted research aimed at finding the most suitable nanoparticles for introduction of magnetic pinning into MgB 2 [13][14][15][16][17][18][19]. The idea of magnetic-type pinning in MgB 2 is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…This is explained with limited growth of MgB2 grains, due to the formation of earlier mentioned nanoprecipitates at grain boundaries. Furthermore, the mean size of hexagonal shapes for both MgB2 samples (Samples 1 and 2), which should correspond to MgB2 grains according to study from our previous works, [16,17] was determined from FE-SEM micrographs, as shown in Figures 3 (a) and 4 (a), respectively. The size distributions of corresponding measured diameters of hexagonal grains are shown in Figures 5 and 6.…”
Section: Xrd and Fe-semmentioning
confidence: 97%
“…The study of the influence of the magnetic nanoparticles addition on electromagnetic properties of MgB2 is given elsewhere. [15][16][17][18] The MgB2 sample, formed after the addition of NiCoB nanoparticles (2.67 w. %) to Mg and B precursor powders and sintering at 650 C, which represent the subject of this research, was chosen due to the observed improvement of critical current density in respect to the MgB2 sample without the addition of the nanoparticles. [15] Generally, the identification of all phases present in the resulting MgB2 samples formed after the addition of the nanoparticles with various chemical composition to MgB2 precursor powders (sintered at various temperatures), along with the determination of their morphologies and dimensions, is crucial in understanding and interpreting the observed changes in the superconducting properties of MgB2 (either positive or negative ones).…”
Section: Introductionmentioning
confidence: 99%